Study the level of microbial and chemical pollutants in the soil of some densely populated areas of Baghdad - Hameda Khadem Zgair (World Journal of Experimental Biosciences, 2025)
The problem of environmental pollution with heavy metals and pathogenic microorganisms, especially soil contamination, is considered one of the most important public health threats. The current study aims to evaluate the levels of soil contamination in densely populated areas of Baghdad with heavy metals and pathogenic microorganisms and evaluate the incidence of skin infection with different microorganisms in the study areas. Fifty soil samples were collected from different regions of Al-Sadr City and the areas east of the canal. The atomic absorption spectrometer was used to measure the level of heavy metals [Cooper (cu), Zinc (Zn), Lead (Pb), Cadmium (cd), and Mercury (Hg)]. Routine microbiological techniques were used to evaluate the levels of soil contamination with different microorganisms, and the same methods were used to isolate and identify the microorganism causing skin infection in 75 skin swabs collected from outdoor patients of the same study's area. The results of the current study showed that heavy metal levels in the soil samples were below the permissible limits by the United States Environmental Protection Agency (EPA) document. The study also showed that most soil samples were contaminated with microorganisms, particularly normal flora bacteria, at high levels, followed by actinomycetes, whereas contamination with coliform bacteria was very low. The results of microbial examination of the skin showed that the fungal infection was followed by a bacterial infection (Staphylococcal infection), whereas infection with Escherichia coli was the lowest. The current study concludes that soil contamination levels in densely populated areas of Baghdad are within acceptable limits. The study also showed that microbial contamination with fecal microorganisms was low.
Keywords: Heavy metals, Microorganism, Pollution, Skin infection